Factors Influencing Completion of Non-Governmental Projects in Rwanda. A Case of the Society for Family Health Rwanda's Youth Employment Project - Uwitonze, Stella; Irechukwu, Eugenia (International Journal of Entrepreneurship and Project Management, 2024)
Purpose: This study aimed to investigate the factors affecting the completion of NGO projects in Rwanda, with a focus on funding, stakeholder participation, project communication, and effective planning. Methodology: The study employed a descriptive research design and was grounded in Rational Choice Theory, Resource Dependence Theory, Communications Theory, and Theory of Constraints. Data were collected from 180 employees of the Society for Family Health Rwanda using semi-structured questionnaires. The data were analyzed using SPSS version 25, incorporating descriptive statistics and regression analysis. Findings: The findings revealed that funding levels had a positive but statistically insignificant effect on project completion (β = 0.080, p > 0.05). Stakeholder participation exhibited a negative but statistically insignificant relationship (β = -0.056, p > 0.05). However, project communication emerged as a significant predictor, showing a negative standardized coefficient (β = -0.421, p < 0.001), indicating that ineffective communication adversely impacts project completion. Effective planning demonstrated the strongest positive association with project success (β = 1.042, p < 0.001). Unique Contribution to Theory, Practice and Policy: To enhance project completion rates, NGOs in Rwanda should prioritize meticulous planning, as it significantly influences project success. Additionally, improving communication strategies is essential to address the negative impact of ineffective communication on project outcomes. While funding and stakeholder participation showed no significant effects, efforts should still be made to optimize these factors to support project execution.